Quantitative study about the role of environmental conditions in the survival capability of multidrug-resistant bacteria - Adrienn Hanczvikkel; Ákos Tóth (Elsevier, 2018)
Background: Healthcare-associated infections (HAIs) caused by multidrug-resistant bacteria (MDRB) are of global concern and hospital textiles can contribute to their transmission. MDRB are able to survive on textiles for more than enough time to spread in the environment. Some studies summarized the effect of environmental factors on the duration of bacterial survival, but it remained an open question how these factors influence the quantity of surviving bacteria in a period of a few days, which is relevant from the perspective of HAIs. Investigating this effect can contribute to better understand the spread of MDRB and the emergence of hospital outbreaks. Methods: We investigated quantitatively the survival capability of 15 vancomycin-resistant Enterococcus faecium (VRE), 15 methicillin-resistant Staphylococcus aureus (MRSA), 15 multidrug-resistant Acinetobacter baumannii (MACI) and 15 multidrug-resistant Klebsiella pneumoniae (MRKP) in five environmental conditions using the plate count method. We examined the role of nutrients, textile types, temperature and level of relative humidity on bacterial survival after 1-7 days of incubation. Results: Each bacterial group showed higher survival capability on 100% cotton towel than on 100% cotton sheet (P < 0.01). MRSAs and VREs showed higher (P < 0.01), MACIs showed lower (P = 0.02) CFU/swatch values on 100% polyester sheet than on cotton sheet. The survival capability of MRKPs and MRSAs was higher inoculated in nutrient broth than in saline solution (P < 0.01). Each bacterial group showed lower survival capability (P < 0.01) at body condition (T = 35 °C, Rh = 83%) than at control (T = 25 °C, Rh = 52%). Conclusions: Towels proved to be excellent conditions for each bacteria to survive, however chemical composition of the textiles affected differently the survival of Gram-positive and Gram-negative bacteria. These findings could be useful in searching for the source of outbreaks. Organic contamination of the textiles can increase the survival of desiccation-sensitive bacteria, therefore nutrient-rich inoculating medium is recommended in survival studies. Keywords: Healthcare-associated bacteria, Survival capability, Textiles, Environmental factors